2005
DOI: 10.1016/j.ccr.2005.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Early inactivation of p53 tumor suppressor gene cooperating with NF1 loss induces malignant astrocytoma

Abstract: Malignant astrocytoma, the most prevalent primary brain tumor, is resistant to all known therapies and frequently harbors mutations that inactivate p53 and activate Ras signaling. We have generated mouse strains that lack p53 and harbor a conditional allele of the NF1 tumor suppressor that negatively regulates Ras signaling. The mice develop malignant astrocytomas with complete penetrance. The majority of tumors display characteristics of glioblastoma multiforme with concomitant alteration of signaling pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
412
2
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 491 publications
(447 citation statements)
references
References 54 publications
32
412
2
1
Order By: Relevance
“…Further, we examined Notch1 expression in the Mut3 (cisp53 þ /À ;NF1 þ /flox hGFAP-cre) glioma mouse model. 18 These mice develop malignant astrocytomas with complete penetrance because of the loss of p53 and Nf1. Levels of Notch1 and NICD were substantially increased in primary glioma tissue (World Health Organization grade IV) from Mut3 mice compared with brain tissue of control mice (Figure 1e).…”
Section: Elevated Notch1 Expression Is a Feature Of Glioblastomamentioning
confidence: 99%
See 1 more Smart Citation
“…Further, we examined Notch1 expression in the Mut3 (cisp53 þ /À ;NF1 þ /flox hGFAP-cre) glioma mouse model. 18 These mice develop malignant astrocytomas with complete penetrance because of the loss of p53 and Nf1. Levels of Notch1 and NICD were substantially increased in primary glioma tissue (World Health Organization grade IV) from Mut3 mice compared with brain tissue of control mice (Figure 1e).…”
Section: Elevated Notch1 Expression Is a Feature Of Glioblastomamentioning
confidence: 99%
“…The knockdown of Notch1 induced apoptosis in 15 to 20% of U251MG cells and 20 to 30% of U373MG cells, but had no apoptosis-inducing effect in U87MG, LN229, NCH89 and NCH468 cells (Supplementary Figure S1). To explore whether Notch1 signaling modulates the resistance to apoptosis in 18 (five independent tumor samples) and non-tumor brain tissue from control mice (five independent tissue samples). Expression data were normalized to internal GAPDH mRNA levels (n ¼ 3; mean ± s.d.).…”
Section: Elevated Notch1 Expression Is a Feature Of Glioblastomamentioning
confidence: 99%
“…In other hematopoietic malignancies, an initiating lesion in self-renewing stem cells may progress to malignancy when coupled with increased mutagenic events in the more rapidly expanding progenitor pool (Bonnet and Dick 1997;Cozzio et al, 2003;Rossi et al, 2008). Similarly, adult SVZ NSCs have been proposed as the origin of gliomas and astrocytomas (Lewis 1968;Vick et al, 1977;Holland et al, 2000;Sanai et al, 2005;Zhu et al, 2005;Jackson et al, 2006). Brain tumor cells share both anatomical location with SVZ niches and similar properties, including dependence on signaling pathways regulating normal NSC self-renewal Lim et al, 2007).…”
Section: Chromatin Aging Stem Cells and Tumor Developmentmentioning
confidence: 99%
“…By creating a series of mouse models harboring conditionally deletable Pten (20) or Nf1 allele (21) and conditionally activatable mutant LSL-K-ras G12D alleles (22), we demonstrated that loss of expression of Pten, the second most frequently mutated tumor suppressor gene in all human cancers, in combination with K-RAS activation, led to the development of NFs with 100% penetrance, followed by MPNST transformation. Importantly, MPNST development correlates with loss of PTEN expression in both our murine model as well as human NF1 patients and can be visualized via noninvasive (Fig.…”
mentioning
confidence: 99%